If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-1)=3(x-2)
We simplify the equation to the form, which is simple to understand
6(x-1)=3(x-2)
Reorder the terms in parentheses
+(+6x-6)=3*(x-2)
Remove unnecessary parentheses
+6x-6=+3+*(+x-2+)
Reorder the terms in parentheses
+6x-6=+(+3x-6)
Remove unnecessary parentheses
+6x-6=+3x-6
We move all terms containing x to the left and all other terms to the right.
+6x-3x=-6+6
We simplify left and right side of the equation.
+3x=0
We divide both sides of the equation by 3 to get x.
x=0
| 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 | | 6x-5=4x-9 | | 3/4x-1+1/2x=7/16x+1/8 | | 1/2(x-6)=9 | | 5(y-4)=2(y+5)Y | | f(x)=x^3-x^2-11x+3 | | 5/6*2/3*2/7 | | x=(2.4e)/(0.68^1/5) | | 3/5*4/7*1/3 | | -9x^2+16x-14=0 | | 5(2x+3)=7(x+1) | | 0.11+0.09+720=1520 | | 17x+27x=180 | | 9/10*5/7*1/3 | | -16+2x=4x-4(4+3) | | 4x^2-15x+14=-6x+9 | | x=2.4e/(0.68)^1/5 | | -15+2x=45 | | -6x^2-23x-4=0 |